Financing higher education through waqf in Pakistan : issues and challenges - Muhammad Usman,; Asmak Ab Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper aims to study various issues waqf faces in general in Pakistan and probes in particular impediments and challenges to waqf funding in higher education. The paper formulates its arguments and results on the basis of information gleaned from twelve interviewees, archival records, documents and library sources. It looks at the subject matter from three different perspectives; government, waqf for higher educational institutions and general society. Waqf practice for higher education in Pakistan is largely restricted to private sector and is marred by various issues and challenges, including lack of legal framework and government support. Equally, lack of transparency and fears of centralisation have stifled its integrity and prospects for growth. Since society does not fully grasp waqf assets’ eternal nature characterised by perpetuity, irrevocability and inalienability, most of the waqf assets fail to receive sustained support. These challenges can be overcome through proper planning, understanding, and awareness of waqf. Hence, it is the responsibility of the government to make laws and provide a feasible environment for waqf practice in higher education funding as a third sector.